Behind the Times inside the new New York Times - Diamond, Edwin (Univ. of Chicago Press, 1995)
An incisive examination of the world's most respected paper, Behind the Times tells the story of changing Timesian values and of a new era for the paper--a tale of editorial struggles, star columnists and critics, institutional self-importance, and the political and cultural favorites of the Times' owners and editors. Taking the reader inside the Times' newsrooms and executive offices, Diamond offers an expert, insider's appraisal of how the Times and its editors continue to shape coverage of major public events for over one million readers. Diamond goes behind the scenes to recount the paper's recent and much heralded plan to win larger audiences and hold on to its dominant position in the new media landscape of celebrity journalism and hundred-channel television. "Edwin Diamond's Behind the Times sets the Paper of Record straight--a fascinating look at the people and policies, the dissension and debate behind the seemingly serene masthead of the New York Times. No newsroom is a Garden of Eden, and only the rare reporter wears a halo: the Times, not surprisingly, is an imperfect place. But Edwin Diamond is careful to note the triumph as well as the turmoil at this great American newspaper. The result is a window on the changing world of journalism today."--Dan Rather.
Keywords: New York times; The New York Times; Geschichte 1970-1993; New York Times; Hochschulschrift